Individual behavior and group membership: Comment - Matthias Sutter (University of Innsbruck, Department of Public Finance, 2008)
Charness et al. (2007b) have shown that group membership has a strong effect on individual decisions in strategic games when group membership is salient through payoff commonality. In this comment I show that their findings also apply to non-strategic decisions, even when no outgroup exists, and I relate the effects of group membership on individual decisions to joint decision making in teams. I find in an investment experiment that individual decisions with salient group membership are largely the same as team decisions. This finding bridges the literature on team decision making and on group membership effects.
Keywords: C91; C92; D71; 330; Entscheidung bei Risiko; Gruppenentscheidung; Stochastischer Prozess; Test